Preparation of Four Chromium Ore Reference Materials. Issue 1 (11th March 2013) - Cheng, Zhizhong; Huang, Hongku; Liu, Mei; Gu, Tiexin; Yan, Weidong; Yan, Mingcai
<x xml:space="preserve">Abstract</x> The preparation and characterisation of four chromium ore reference materials are described in this paper. The sample material for GCr‐1, GCr‐3 and GCr‐4 was collected from chromite deposits in Tibet, Qinghai province and Inner Mongolia. GCr‐2 is a composite sample from GCr‐1 and GCr‐4. Sample homogeneity was tested by WD‐XRF and the relative standard deviations were < 1.0%. An F‐test showed that all four materials were homogeneous. Thirteen laboratories involved in the inter‐laboratory programme provided 672 determinations (eighteen oxides and elements). Sixteen components were characterised as certified values, of which Cr2O3 ranged from 17.59 to 57.80% m/m. The contents of FeO and CO2 were taken as reference values.